2017
DOI: 10.1103/physrevlett.119.060601
|View full text |Cite
|
Sign up to set email alerts
|

Exact Extremal Statistics in the Classical 1D Coulomb Gas

Abstract: We consider a one-dimensional classical Coulomb gas of N like-charges in a harmonic potential -also known as the one-dimensional one-component plasma (1dOCP). We compute analytically the probability distribution of the position xmax of the rightmost charge in the limit of large N . We show that the typical fluctuations of xmax around its mean are described by a non-trivial scaling function, with asymmetric tails. This distribution is different from the Tracy-Widom distribution of xmax for the Dyson's log-gas. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 52 publications
3
74
0
Order By: Relevance
“…It would be interesting to explicitly check this, by adding a FI parameter in [25] and doing the corresponding analysis. Finally, it is worth mentioning that at first apparently unrelated works in statistical mechanics, study in fact similar problems and systems [29,30]. and the saddle point equation reduces to the trivial expression f ≡ 0.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to explicitly check this, by adding a FI parameter in [25] and doing the corresponding analysis. Finally, it is worth mentioning that at first apparently unrelated works in statistical mechanics, study in fact similar problems and systems [29,30]. and the saddle point equation reduces to the trivial expression f ≡ 0.…”
Section: Discussionmentioning
confidence: 99%
“…What it gives is the probability of an atypically large fluctuation, with the greatest eigenvalue moving deep into the bulk of the eigenvalue distribution. This is a q-analogue of the large fluctuations in the GUE discussed in [24,68] (see also [69,70]). Besides, we underline that, differently from [24] where a large deviation from the equilibrium configuration is of order ∼ √ N , in the q-analogue the support of the eigenvalue density grows as N g s , thus large deviations from the equilibrium are of order ∼ N .…”
Section: Csmentioning
confidence: 76%
“…An example of an interesting question that one could ask is regarding the distribution of the edge particle which is known to be of the Tracy-Widom form for the log-gas. In a recent paper the question of universality of this result for general 1D interacting systems was investigated and it was shown that the form is in fact very different for a 1D coulomb gas (interaction potential between particles given by modulus of distance) [35]. In the present paper we ask the same question for the Calogero-Moser model.…”
Section: Introductionmentioning
confidence: 72%